2018
DOI: 10.3892/br.2018.1070
|View full text |Cite
|
Sign up to set email alerts
|

Association of P53 gene polymorphism with gastric cancer in Northern Iran as a high‑risk region

Abstract: Abstract. Gastric cancer has the fourth highest morbidity rate of all cancers worldwide. Genetic factors including alterations in oncogenes and tumor suppressor genes serve an important role in gastric cancer development and progression. The P53 gene acts as a tumor suppressor gene by regulating the cell cycle, DNA transcription and repair, apoptosis, senescence and genome stability. In addition to somatic P53 mutations in cancer development, germline polymorphisms are also involved in different malignancies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Although the differences were not statistically significant, the overall survival rates of both GC and EC patients with p53 positive expression were higher than those with p53 negative expression, which was consistent with Wang's and Li's [41 , 42] investigations among 2,013 renal cell carcinoma patients and 150 GC patients, respectively. However, although some groups also reported that rs1042522 had an effect on cancer survival[34 , 43], we did not find any relationship between this SNP and survival of GC or EC, which was consistent with the results from Hedayatizadeh-Omran et al [44].…”
Section: Discussionsupporting
confidence: 92%
“…Although the differences were not statistically significant, the overall survival rates of both GC and EC patients with p53 positive expression were higher than those with p53 negative expression, which was consistent with Wang's and Li's [41 , 42] investigations among 2,013 renal cell carcinoma patients and 150 GC patients, respectively. However, although some groups also reported that rs1042522 had an effect on cancer survival[34 , 43], we did not find any relationship between this SNP and survival of GC or EC, which was consistent with the results from Hedayatizadeh-Omran et al [44].…”
Section: Discussionsupporting
confidence: 92%
“…Gastric cancer (GC) ranks as the second most prevalent malignancy worldwide and has the fourth highest morbidity rate [1,2]. The incidence of GC differs heterogeneously in different countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…3 Gastric cancer is a multifactorial disorder, with aging, male sex, lifestyle, environmental and genetic factors, and Helicobacter pylori infection among its known risk factors. 9 Gastric cancer is characterized by nonspecific symptoms such as dyspepsia, weight loss, and anemia, making its early detection and diagnosis difficult. Therefore, when the disease is diagnosed it is usually advanced, and treatments become more complex and costly.…”
Section: Introductionmentioning
confidence: 99%